The convention on the rights of persons with disabilities versus the right to health care - Baranauskienė, Ingrida (Social Welfare: Interdisciplinary Approach, 2019)
By employing the research methodology of thematic analysis, the paper presents the investigation of the Convention on the Rights or Persons with Disabilities in the aspect of the right to health care. The revealing of fundamental resolutions of the Convention on the Rights of Persons with Disabilities, manifestation of them in the aspect of the health care system are the object of the present paper; moreover, these emphasise the social relevance seeking to ensure comprehensive and equal use of all human rights and fundamental freedoms, dignity, full participation in public life and, naturally, health care system for persons with disabilities. The research problem is formulated within this context: What resolutions of the Convention on the Rights of Persons with Disabilities are the most important to successfully ensure persons’ with disabilities rights to health care? What is the semantic manifestation of these resolutions and what are the contexts that ensure successful implementation of them?
Keywords: The Convention on the Rights of Persons with Disabilities; Right to Health Care; Equal Rights